Phenomenology Study: Factors Associated with the Choice of Unskilled Traditional Birth Attendants in Brebes, Central Java - Prastiwi, Ratih Sakti; Budihastuti, Uki Retno; Wijaya, Mahendra (Journal of Maternal and Child Health, 2016)
Background: The number of birth delivery attended by unskilled traditional birth attendant in Brebes District, Central Java, was still high. From January to April 2016, 67 birth deliveries were attended by unskilled traditional birth attendant. This study aimed to delve information in how social and cultural factors influence the decision to choose traditional birth attendants in Brebes, Central Java. Subjects and Method: This was a qualitative study with phenomenology approach. This study was carried out in Brebes, Central Java. The key informants of this study were midwives, who by snowball sampling technique suggested on the traditional birth attendants and their clients (i.e. laboring mothers) to be interviewed. The data were collected by in-depth interview, focus group discussion, observation, and document review. The researcher did data reduction, data display, and made decision. The data were verified by triangulation of sources technique. Results: Some skilled traditional birth attendants actively collaborated with midwives. Today rarely traditional birth attendants attend birth delivery, although there was a considerable number of community members who sought their help for birth attendant. Community members regard these traditional birth attendants as to have charisma and some supernatural power. Usually traditional birth attendants get involved in cultural ceremonies. Sometimes community members seek traditional birth attendants as a source of advice. In an extended family the decision to choose birth attendant was made by the mother or grandmother of the laboring woman. In a smaller family the decision to choose birth attendant was made by the laboring woman. Conclusion: The decision to choose unskilled birth attendants is made by the family members of the laboring woman, and this choice was influenced by traditional birth attendant